Connecting the dots between computational tools to analyse soil–root water relations. (17th October 2018) - Passot, Sixtine; Couvreur, Valentin; Meunier, Félicien; Draye, Xavier; Javaux, Mathieu; Leitner, Daniel; Pagès, Loïc; Schnepf, Andrea; Vanderborght, Jan; Lobet, Guillaume
Abstract : Many computational tools exist to quantify water flow in the soil–root system. These tools can be arranged in a comprehensive network that can be leveraged to better interpret experimental data. Abstract: In recent years, many computational tools, such as image analysis, data management, process-based simulation, and upscaling tools, have been developed to help quantify and understand water flow in the soil–root system, at multiple scales (tissue, organ, plant, and population). Several of these tools work together or at least are compatible. However, for the uninformed researcher, they might seem disconnected, forming an unclear and disorganized succession of tools. In this article, we show how different studies can be further developed by connecting them to analyse soil–root water relations in a comprehensive and structured network. This 'explicit network of soil–root computational tools' informs readers about existing tools and helps them understand how their data (past and future) might fit within the network. We also demonstrate the novel possibilities of scale-consistent parameterizations made possible by the network with a set of case studies from the literature. Finally, we discuss existing gaps in the network and how we can move forward to fill them.